A Descriptive Examination of Nonmedical Fentanyl Use in the United States: Characteristics of Use, Motives, and Consequences. (July 2018) - Kilwein, Tess M.; Hunt, Preston; Looby, Alison
Little is currently known about nonmedical fentanyl use (NFU; that is, use of illicit or pharmaceutically produced fentanyl without a prescription or in ways other than prescribed) despite increases in prevalence and consequences (e.g., overdose, fatality). Individuals with a lifetime history of NFU ( N = 122) in the United States completed an online survey assessing demographics and factors related to use. Results revealed diversion of prescriptions, unintentional use of illicit fentanyl, and high co-occurrence of mental illness and other illicit substance use among users. Commonly reported motives reflected negative/positive reinforcement (e.g., to relieve stress, to get high) and relieving pain/physical discomfort, regardless of frequency of use. More severe consequences (e.g., increased tolerance, withdrawal) were reported among high frequency users. This descriptive examination of NFU may aid in the identification of individuals at-risk for use, promote an understanding of reasons for use, and guide prevention and intervention developments.